Reposisi peran perpustakaan tinggi (Sebuah catatan kunjungan) - Wiji Suwarno (Libraria: Jurnal Ilmu Perpustakaan dan Informasi, 2022)
This paper raises the theme of repositioning the role of university libraries based on observations from a visit to Jawaharal Nehru University, New Delhi, India. The author assumes that some of these role repositioning strategies are possible to be adopted and applied in various universities in Indonesia. This paper describes in general from the observation and interview data obtained. The results of this study reveal that the first JNU library repositioning strategy is to open service hours at prime times, second, to provide a comfortable place to write. Third, facilitating access to global and digital references. Fourth, provide scientific consulting services. And fifth, make the library a laboratory.